Behavioural changes in institutionalised older people: a gender perspective - Pinazo-Clapés, Carolina; Pinazo-Hernandis, Sacramento; Sales, Alicia (Technium Social Sciences Journal, 2020)
There is a need to redefine and improve the treatment and care given in residences for the elderly from a non-pharmacological perspective that fosters person-centred care. In particular, the psychological and behavioural symptoms associated with dementia require a multidisciplinary evaluation to design appropriate interventions. The objective is to evaluate behavioural disorders in a group of residing elderly people and analyse whether the gender of the participants influences the presence of these behaviours. In the methodology, the group is consisted of 450 people, 73.6% women and 26.4% men with an average age of 86.82 (WD=8.22). The results show that women have a greater risk of presenting behavioural disorders. Men tend to present higher levels of anxiety, lack of inhibition, sleeping disorders, and loss of appetite; while women present more affective symptoms such as anxiety, euphoria, or apathy, or more psychotic symptoms such as delusions and hallucinations, and more aberrant motor behaviours. This influence is only significant for delusions and aberrant motor behaviour. The discussion and conclusions of the study show that gender influences behavioural disorders. This type of research work is very scarce because may be of great interest to develop and improve preventive strategies and non-pharmacological use of these symptoms in residence for the elderly settings.